Housing and Household Instability. (May 2016) - Desmond, Matthew; Perkins, Kristin L.
Previous research attempting to estimate the effects of residential instability typically overlooks other consequential changes within households that may be coincident with moving. Drawing on novel data of renting households in Milwaukee that recently relocated ( N = 569), this article establishes the frequency at which residential or housing instability is accompanied by household instability : changes in the composition of adults living under the same roof. We find that most moves are accompanied by household instability and that households with young children are significantly more likely to experience household instability. These findings imply that researchers attempting to isolate the effects of residential instability, especially for children, should account for the possible influence of household change.